1992
DOI: 10.1007/bf00245213
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the rpoN (hno) gene region of Alcaligenes eutrophus: evidence for a conserved gene cluster

Abstract: The nucleotide sequence of the rpoN gene, formerly designated hno, and flanking DNA regions of the aerobic hydrogen bacterium Alcaligenes eutrophus has been determined; rpoN codes for the RNA polymerase sigma factor sigma 54 involved in nitrogen regulation and diverse physiological functions of gram-negative bacteria. In A. eutrophus hydrogen metabolism is under control of rpoN. The Tn5-Mob insertion in a previously isolated pleiotropic mutant was mapped within the rpoN gene. The derived amino acid sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The cloned DNA fragment contains 262 bp of the 5Ј noncoding sequence. Ϫ24/Ϫ12 motifs characteristic of 54 promoters are located upstream of the translational start of the first structural gene, hoxF (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cloned DNA fragment contains 262 bp of the 5Ј noncoding sequence. Ϫ24/Ϫ12 motifs characteristic of 54 promoters are located upstream of the translational start of the first structural gene, hoxF (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing revealed that hoxA encodes a member of the NtrC family of regulatory proteins (12), suggesting a model for hydrogenase regulation that involves transcriptional activation via binding of HoxA upstream of 54 promoters and interaction with 54 RNA polymerase. In order to test the binding of HoxA to hox upstream sequences in vitro, we attempted to purify HoxA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One additional ORF was however present in R. metallidurans CH34 (orf95), at the same relative location as orf99, present near rpoN in R. eutropha H16 (Warrelmann et al, 1992). Despite their nucleotide sequence similarity, CH34 orf95 and H16 orf99 translated into products which displayed no similarity with each other or any protein in the databases.…”
Section: Discussionmentioning
confidence: 99%